Pengaruh Lama Penutupan Sungkup terhadap Pertumbuhan Stek Mawar (Rosa sp.) - Rinanto, Yudi; Mufida, Aulia; Rahmawati, Dwi Septyana; Muyasaroh, Yuni Faridatul (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2022)
Rose (Rosa sp.) is one of the ornamental plants that are widely cultivated in Indonesia because it has high economic value. The increasing market demand and the still low production of roses requires innovation in the development of rose cultivation, especially vegetatively in the form of cuttings. The purpose of this study was to determine the effect of lid closure on rose cuttings. This research was conducted on rose cuttings by giving the hormone Rhizattun F with a concentration of 500 ppm was soaked for 10 minutes. The results showed that the percentage of live rose cuttings with 2 weeks of lid closure was 62.5% while the percentage of live rose cuttings with 4 weeks of lid closure was 90%. The average number of roots at 2 weeks of mask closure was 2.74 while the average number of roots with 4 weeks of mask closure was 4.95. The average root length of the results showed that the roses at 2 weeks of lid closure had an average length of 2.54 cm while those with 4 weeks of lid closure had an average length of 8.11 cm. The average number of leaves on roses with 2 weeks of lid closure was 1.63, while that of roses with 4 weeks of lid closure was 4.24. The results showed that 4 weeks of mask closure was better than 2 weeks of mask closure.